CORRELATION AGE AND PARITY WITH HIPEREMESIS GRAVIDARUM - Martin Andi Hamdjang; Tafsil Tafsil (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
Background : Hyperemesis Gravidarum is defined as a complication of nausea and vomiting during pregnancy. One of the pregnancy complications that affect the health status of the mother and fetal development is Hyperemesis Gravidarum which can be detected and prevented during pregnancy, where nausea and vomiting occur in 60-80% of primigravidas and 40-60% of multigravidas. The research objective was to determine the relationship between age and parity with the incidence of hyperemesis gravidarum in pregnant women. Method :This type of research design used is a quantitative method using a retrospective approach. The population in this study were all 596 pregnant women patients at Elisabeth Hospital, and the sample was taken using a random sampling technique of 86 respondents. This research was carried out for 6 months in RS ST. Elisabeth Batam City, data analysis using Chisquare and presented in univariate and bivariate tables. Result : Based on the results of the study, it was found that the majority of mothers aged <20 and> 35 years were in the highest category, as many as 58 people (67%), and mothers who worked with 58 people (67%) and mothers with primigravida 50 people (58%). conclusion : The conclusion in this study is that there is a relationship between age and parity with the incidence of hyperemesis gravidarum. The results of this study are expected to be used as a guide and can add knowledge and reference material for further research, especially those related to Hyperemesis Gravidarum.